Aplikasi Absensi Guru Dan Siswa Menggunakan Gps Berbasis Android Di Sma Al-Husna Tangerang - Putri, Alfiana Tiara; Mahmudin, Mahmudin; Mursyidin, Imam Halim (Universitas Islam Syekh Yusuf Tangerang, 2025)
The manual attendance system at SMA Al-Husna Tangerang often causes delays in data recapitulation, potential manipulation, and low efficiency. This study aims to develop an Android-based attendance application utilizing GPS for location validation, addressing the limitations of manual methods and previous systems without location verification. The application was designed using the Extreme Programming (XP) method and tested through Black Box Testing to assess functionality, as well as the System Usability Scale (SUS) to evaluate ease of use. The results show that all features performed as intended, with a SUS score of 80.83%, categorized as Good Usability. These findings indicate that the developed system effectively improves the accuracy, efficiency, and transparency of the attendance process, while preventing fraudulent attendance from outside the school area